Comparative study on pressure sensors for sloshing experiment. (15th January 2015) - Kim, Sang-Yeob; Kim, Kyong-Hwan; Kim, Yonghwan
Abstract: This study considers a comparative study on pressure sensors for the measurement of sloshing impact pressure. For the comparative study, four pressure sensors are used: one piezoresistive sensor, one piezoelectric sensor, and two integrated circuit piezoelectric (ICP) sensors. For the comparative study, the sensors are installed on tank wall and ceiling of a rectangular tank with narrow breadth. Several types of comparative studies are carried out, including the sensitivity to temperature differences between the sensors and test medium. The forced regular and irregular motions are applied to the tank with partial water filling, and pressure signals on the tank due to sloshing are measured at different filling conditions. The characteristics of the pressure sensors are discussed and the measured pressure signals are compared. The measured impact peaks are statistically analysed and the results are compared to observe the difference of sensors. Highlights: Sensitivity to pressure sensor has been systematically tested for sloshing model test. Several different sensors have been tested to observe thermal sensitivity and capability to capture impact signal. The pressure signals measured at the same test condition have been compared. Piezoelectric-type sensors are sensitively to thermal difference of fluid and sensor. This article provides very useful information for model-scale sloshing experiment.